Peran digital marketing pada UMKM di Kedai Kopi 272 - Muhamad Ramadhan, Dimas; Permana Yusuf, Budi (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
UMKM are one of the business sectors that have an important role in economic growth in Indonesia, technological developments and the Covid-19 pandemic have changed UMKM marketing which was originally done face-to-face to digital. Digital marketing is the main key in determining the success of an UMKM business. This study aims to describe the role of digital marketing in marketing a product at Kedai Kopi 272, this study uses descriptive qualitative methods to explain and answer in more detail the problems to be studied and use several data collection techniques, including interviews, observations, and documentation of 3 (three) informants, namely Reza Nurhakim, Lana, and Dini Noviani. The results of this study are the increased sales of Kedai Kopi 272 in March, April and May after using digital marketing to market their products through social media Instagram. This proves that digital marketing has a role in marketing a product at Kedai Kopi 272.